Racial and ethnic disparities in the incidence, healthcare utilization, and outcomes of retained placenta among delivery hospitalizations in the United States, 2016-2019 - Wen Jiang; Wei Chen; Dong Li (BMC, 2023)
Abstract Background Retained placenta is a concern during labor and delivery. However, recent data regarding the profiles of retained placenta are scarce, especially nationwide and in minority populations. This study aimed to investigate the recent incidence of retained placenta and its associated outcomes. Methods We retrospectively analyzed an American population-based data from the National Inpatient Sample (NIS) 2016-2019. The outcomes of interest included the incidence of retained placenta, in-hospital mortality, length of hospital stay, and hospitalization costs. We estimated the incidence for retained placenta overall and by racial and ethnic subgroups, utilizing survey weights standardized for each subgroup. Multivariable linear or logistic regression models were employed in our study to investigate the associations between retained placenta and the impact of in-hospital mortality, duration of stay, and hospitalization expenditures for the entire population and further stratified by race and ethnicity, adjusting for potential confounders. Results Of the 13,848,131 deliveries, there were 108,035 (or 0.78%) birthing persons were identified as having retained placentas. Over time, the incidence of retained placenta increased from 730 per 100,000 (0.73%) in 2016 to 856 per 100,000 (0.86%) in 2019. Native American mothers have the highest rate of retained placenta, with a prevalence almost twice that of the general population, reaching 1,434 cases per 100,000 (1.43%). After adjusting for confounding factors, Native American mothers were more likely to have retained placenta (odds ratio [OR], 1.56; 95% confidence interval [CI], 1.35-1.81), whereas Black (OR, 0.92; 95% CI, 0.88-0.97) and Hispanic mothers (OR, 0.84; 95% CI, 0.80-0.89) were significantly less likely to have retained placenta than White mothers. Furthermore, those who delivered with a retained placenta were significantly associated with higher in-hospital mortality, a longer duration of stay, and hospitalization expenditures, which were disproportionately varied by maternal race and ethnicity. Conclusions The incidence of retained placenta among people undergoing vaginal delivery is exhibiting an upward trend over time, with notable variations observed across different ethnic groups by unclear mechanisms. The ramifications of these findings have the potential to impact the clinical management of maternal health care and the creation of health policies, specifically in relation to the Native American birth population.